Diseño de itinerario de formación preventiva para lideres juveniles en el oratorio Don Bosco de Ibarra - Sandoval, Janeth (2012)
The community provides all the options fall into the worls of drugs, including smoking, alcohol and illegal drugs are readily available at any bar, club or on the streets, the teens feel the abandonment and loneliness for the problems traditional: broken homes, alcoholic or drug addicts parents, are the first damage. In view of inadequate prevention education on alcohol and drugs in the same households and institutions, many teenagers and young people have overcome these problems and not drop out get into trouble with the law, don’t have illegitimate children, nor commit suicide. Unfortunately, a considerable number of young people have fallen into this world of drugs that carry the above problems.